2019
DOI: 10.3390/insects10100325
|View full text |Cite
|
Sign up to set email alerts
|

Cleonis pigra (Scopoli, 1763) (Coleoptera: Curculionidae: Lixinae): Morphological Re-Description of the Immature Stages, Keys, Tribal Comparisons and Biology

Abstract: Mature larvae and pupae of Cleonis pigra (Scopoli, 1763) (Curculionidae: Lixinae: Cleonini) are morphologically described in detail for the first time and compared with known larvae and pupae of other Cleonini species. The results of measurements and characteristics most typical for larvae and pupae of Cleonini are newly extracted and critically discussed, along with some records given previously. Keys for the determination of selected Cleonini species based on their larval and pupal characteristics are attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Efecto del cambio climático sobre insectos plagas, patógenos y plantas invasivas. El cambio climático no solo generará el desplazamiento de bosques y comunidades vegetales alpinas sino que provocará efectos adicionales con el desplazamiento de insectos plaga, patógenos y plantas invasivas (Dukes et al , 2009;Smith-McKenna et al , 2014) . Estas especies si son plagas de los frailejones acelerarán la transformación de los páramos en pastizales.…”
Section: Resultados Cambio Climático Global Como Factor De Predisposición Al Declive Y Muerte De Los Frailejonesunclassified
“…Efecto del cambio climático sobre insectos plagas, patógenos y plantas invasivas. El cambio climático no solo generará el desplazamiento de bosques y comunidades vegetales alpinas sino que provocará efectos adicionales con el desplazamiento de insectos plaga, patógenos y plantas invasivas (Dukes et al , 2009;Smith-McKenna et al , 2014) . Estas especies si son plagas de los frailejones acelerarán la transformación de los páramos en pastizales.…”
Section: Resultados Cambio Climático Global Como Factor De Predisposición Al Declive Y Muerte De Los Frailejonesunclassified
“…In the field, larvae of Curculionid species on plant roots can be difficult to distinguish, as Klapal et al (2004) also noted that the larvae found could not be identified more precisely. Identifying the immature stages of soil-living Curculionidae requires knowledge and experience (Gosik et al 2016;Skuhrovec et al 2019). However, sugar beet weevil larvae can orientate themselves by chemotactic stimuli of the root exudates and actively migrate to the plant roots (Auersch 1961b).…”
Section: Discussionmentioning
confidence: 99%
“…El desarrollo de las larvas de entiminae en las plantas de frailejón provocaría la formación de agallas o proliferación de raíces laterales para subsanar el consumo del insecto considerando la información reportada para curculionidos consumidores de raíces (Skuhrovec et al , 2019) . Sin embargo hasta el momento no existen reportes de observación de agallas o proliferación de raíces en las plantas de frailejón y en consecuencia no existe evidencia para afirmar que los entiminos están infectando las raíces.…”
Section: Factores Bióticos Contribuyentes Al Declive Y Muerte De Los Frailejonesunclassified